7x+8(9x+57)=-18

Simple and best practice solution for 7x+8(9x+57)=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+8(9x+57)=-18 equation:


Simplifying
7x + 8(9x + 57) = -18

Reorder the terms:
7x + 8(57 + 9x) = -18
7x + (57 * 8 + 9x * 8) = -18
7x + (456 + 72x) = -18

Reorder the terms:
456 + 7x + 72x = -18

Combine like terms: 7x + 72x = 79x
456 + 79x = -18

Solving
456 + 79x = -18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-456' to each side of the equation.
456 + -456 + 79x = -18 + -456

Combine like terms: 456 + -456 = 0
0 + 79x = -18 + -456
79x = -18 + -456

Combine like terms: -18 + -456 = -474
79x = -474

Divide each side by '79'.
x = -6

Simplifying
x = -6

See similar equations:

| 44/8.75 | | -4/(x^2-4)=0 | | 2x+(x+3)/6=4 | | 1/7(x-10)=7 | | 38.25=4.5(6.4+x) | | 3.2c-18.2c+13.27=-15.7c+10.05 | | 3x^2=x-1 | | 5(2x-8)=1/5(30+60) | | -99.999=-5.6x-7.6 | | 6-10/11x=16 | | 24=10-3x | | -6(-3+7x)=144 | | 7(-14)[3(-7)-5(-4)]= | | 9b-17-13b=-17-11b | | 8.75/44 | | ((e^11x)-1)/x | | p+2/8=3/9 | | 12s-17=-13+15s-10 | | x-3/3=x-4/4 | | 19j-8=3+20j+9 | | x-0.5+20=37 | | 2x+3+x+7=90 | | -3(7+x)+8=-3(x+7) | | 12p^2-7p+1=0 | | -19-8t=-11t-1-3 | | f(x)=x^2-5x+7 | | X-9+2wx=u | | 7.1(-8.5+x)=37.63 | | 5x-7+2x+9=6x+2+x | | x+(-2)=-3 | | 1/4w=8 | | 5+20y=16y+y+14 |

Equations solver categories